Penguatan Kapasitas Publikasi Ilmiah melalui Workshop Penulisan Artikel Jurnal Bereputasi bagi Dosen Fakultas Agama Islam Universitas Muhammadiyah Klaten - Suparman, Muh. Fatahillah; Abbas, Ngatmin; Tranggono, Bambang; Muriyanto, Muriyanto (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Scientific publication in reputable journals, both nationally accredited and internationally indexed such as Scopus, remains a challenge for lecturers in the Faculty of Islamic Studies. Results from a pretest involving ten participants showed that one scored 8, while the remaining nine scored 9 or 10 out of 10 questions, indicating a good cognitive understanding of publication fundamentals. However, technical issues persist, such as structuring articles, distinguishing abstracts from introductions, building a strong literature review, and using tools like reference managers, plagiarism checkers, and the Open Journal System (OJS). To address these, a practical and participatory workshop was held, covering material presentation, group discussions, submission simulations, and continued coaching. The post-test results showed an average score increase to 12.4 out of 15. About 60% of participants felt adequately prepared, while 40% felt very ready and optimistic. Most participants felt motivated, gained clear understanding, and received concrete tools for publication. Recommendations included online mentoring, article clinics, involving reviewers, and providing practical modules.